2014
DOI: 10.5324/nje.v24i1-2.1755
|View full text |Cite
|
Sign up to set email alerts
|

The biobank of the Norwegian Mother and Child Cohort Study – present status

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
130
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 11 publications
(15 reference statements)
0
130
0
Order By: Relevance
“…Our study specifically addressed post-separation time delays, as was typical for plasma in the Norwegian Mother and Child Cohort Study 16,26 (eTable 1). Although pre-separation delay may be more relevant for the Danish National Birth Cohort 4,27 , a previous study has indicated that thyroid hormone biomarkers in plasma and sera are similarly stable in room temperature with up to 72 hours delay in blood separation 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study specifically addressed post-separation time delays, as was typical for plasma in the Norwegian Mother and Child Cohort Study 16,26 (eTable 1). Although pre-separation delay may be more relevant for the Danish National Birth Cohort 4,27 , a previous study has indicated that thyroid hormone biomarkers in plasma and sera are similarly stable in room temperature with up to 72 hours delay in blood separation 17 .…”
Section: Discussionmentioning
confidence: 99%
“…At the biobank repository, DNA was extracted and stored at −20°C until analysis. For details of sample handling, see …”
Section: Methodsmentioning
confidence: 99%
“…Blood samples were collected from participants at the time of the routine ultrasound examination and shipped at ambient temperature to the MoBa biorepository in Oslo (22). Samples were collected from women between approximately 17–20 weeks gestation.…”
Section: Methodsmentioning
confidence: 99%